NON-STRABISMIC ANOMALIES OF THE EYES IN PRESCHOOL CHILDREN AND THE DEVELOPMENT OF A TRIPLEX ULTRASOUND EXAMINATION - Kasimov, E.M.; Hajiyeva, S.A.; Salmanova, S.Z.; Hajiyeva, N.R. (World of Medicine and Biology, 2025)
The purpose of the study was to elucidate the profile of non-strabismic binocular vision dysfunction and its relationship with intraorbital hemodynamic features in preschool children. The prospective study conducted on 1000 patients diagnosed with transient ischemic attack in the neonatal period of life, according to the clinical characteristics of the transition from infancy to the preschool stage of life. These patients were examined dynamically (3 months–3 years, and then from 3 to 6 years): determinations of eye refraction, dynamic refraction, the state of the inner membranes of the eyes, the level of constant potentials of the cerebral cortex of brain. The ophthalmic artery blood flow, the vasomotor supply of the eyes, optical-vestibular sensitivity and neuroplasticity variants are assessed. The most common non-strabismic disorders of binocular vision were accommodation spasm (39.0 %), convergence insufficiency (13.6 %), convergence excess (9.1 %), accommodation insufficiency (15.9 %), basic exophoria (3.5 %), basic esophoria (6.1 %), and inferior oblique muscle hyperfunction (6.4 %).
Keywords: binocular vision; non-strabismic disorders; accommodation; transient ischemic attack; children